“Julle is tot vryheid geroep!” Die erediens as lewe in evangeliese vryheid - Van der Merwe, IJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
“Called to freedom!” Worship as Life in the Freedom of the Gospel How is the church’s involvement in social issues to be distinguished from the same involvement by non-Christian organisations? This article postulates that moral behaviour and acts of generosity is only to be called “Christian” with regard to its foundation in the act of worship. The liturgy as acclamation and appropriation of the freedom that Christ bestows on his people is explicated in its dissimilarity to popular notions of freedom. The congregation is considered as a community where the freedom of the gospel is communicated in being “church-for-others”. The Eucharist is characterised as the act where the church is representative of God’s new community of freedom where justice and peace reigns.